2007
DOI: 10.1590/s0100-879x2006005000152
|View full text |Cite
|
Sign up to set email alerts
|

Leptin levels in different forms of Chagas' disease

Abstract: Leptin is produced primarily by adipocytes. Although originally associated with the central regulation of satiety and energy metabolism, increasing evidence indicates that leptin may be an important mediator in cardiovascular pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
11
2
Order By: Relevance
“…At variance with our findings, some authors [21] reported decreased leptin levels in chagasic patients with congestive heart failure, whereas another study [44] showed no differences between CCC patients and controls. In both studies, however, the classification of myocardial involvement was different from the present one [21,44].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At variance with our findings, some authors [21] reported decreased leptin levels in chagasic patients with congestive heart failure, whereas another study [44] showed no differences between CCC patients and controls. In both studies, however, the classification of myocardial involvement was different from the present one [21,44].…”
Section: Discussioncontrasting
confidence: 99%
“…At variance with our findings, some authors [21] reported decreased leptin levels in chagasic patients with congestive heart failure, whereas another study [44] showed no differences between CCC patients and controls. In both studies, however, the classification of myocardial involvement was different from the present one [21,44]. In line with our findings, leptin levels were found increased in non-chagasic individuals with chronic heart failure as a reflection of the proposed hypertrophic effects of leptin on cardiomyocytes [45,46].…”
Section: Discussioncontrasting
confidence: 99%
“…In particular, the concentration of BNP and ANP in serum were systematically studied as markers of heart damage in Chagasic patients (Garcia-Alvarez et al, 2010; Heringer-Walther et al, 2005; Ribeiro et al, 2002) since they had been previously related with cardiovascular diseases (Wang et al, 2006; Wondergem et al, 2001). Increased concentrations of BNP and ANP strongly correlated with the severity of Chagas-associated cardiac damage, being BNP more sensitive than ANP (Fernandes et al, 2007; Heringer-Walther et al, 2005; Talvani et al, 2004b). Upon these findings, the authors proposed that BNP could be measured periodically in asymptomatic patients as screening test to detect incipient ventricular dysfunction (Heringer-Walther et al, 2005).…”
Section: Diagnostic Applications For Chagas D Isease: Pending Issuesmentioning
confidence: 99%
“…Biochemical molecules, such as glutamic oxaloacetic transaminase, glutamic-pyruvic transaminase, alkaline phosphatase, acid maltase, alpha-hydroxybutyric dehydrogenase (or LDH1), leptin, adipokines and angiotensin-converting enzyme, have also been tested in humans to assess early cardiological damage ( Alarcon-Corredor et al 2002 , Combs et al 2005 , Fernandes et al 2007 , Wang et al 2010 ). Nevertheless, there are no reports of studies using these biomarkers to assess therapeutic efficacy.…”
Section: Host Response/damage Biomarkersmentioning
confidence: 99%